Layanan Konseling Kelompok Sebagai Proses Pemecahan Masalah Siswa Kelas XI SMKN I Pacitan Tahun Pelajaran 2016/2017. - Puguh Eksan (Transformasi : Jurnal Studi Agama Islam, 2017)
The objectives of research are : (1) to describe the consular service characteristics ofSMKN I Pacitan students. (2) To describe the characteristics of consular activities in groupconsular service for students of SMKN I Pacitan. The type of the research is qualitativeresearch, by using ethnography approach. The limitaton of the research is group consularservice for grade eleven SMKN I Pacitan students academic year of 2016/2017. The primerdata are obtained from informan, such as, the head waster, teacher, students, and otherstakeholder.Data collection method is by observing, interviewing, and making documentation.Data analysis used in this research is interactive model of analysis. Data validation test usedin this research is credibility, transferability, dependability, and confirmability. The result ofthis research are: (1) the characteristics of consular service in SMKN I Pacitan is that theservice is done by holding group dynamic in the consular room to solve the studentsproblems. (2) The counseling activity in SMKN I Pacitan is begun from identifying thestudents problems, arranging the counseling service program structure, the use of anappropriate service technique and giving feed back to the conseling service result done.